2010
DOI: 10.1186/1471-2334-10-207
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin for Crimean-Congo hemorrhagic fever: systematic review and meta-analysis

Abstract: BackgroundCrimean-Congo hemorrhagic fever epidemics often occur in areas where health services are limited, and result in high case fatality rates. Besides intensive care, ribavirin is often recommended. A solid evidence base for the use of this drug will help justify assuring access to the drug in areas where epidemics are common.MethodsWe carried out a systematic review of observational and experimental studies of people with suspected or confirmed Crimean-Congo hemorrhagic fever that included comparisons be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 47 publications
(87 reference statements)
3
72
0
4
Order By: Relevance
“…Although most reports claimed a therapeutic benefit about ribavirin use, the quality of the evidence was low. In general, treatment of CCHF is mainly supportive therapy 9,10,35,36 . In our study, the case who died did not receive ribarivin therapy and three of CCHF cases received oral ribavirin.…”
Section: Discussionmentioning
confidence: 99%
“…Although most reports claimed a therapeutic benefit about ribavirin use, the quality of the evidence was low. In general, treatment of CCHF is mainly supportive therapy 9,10,35,36 . In our study, the case who died did not receive ribarivin therapy and three of CCHF cases received oral ribavirin.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent attempt to identify a benefit of ribavirin in a randomized clinical trial was unable to show that treatment significantly altered the disease (Koksal et al, 2010). A review of 21 published observational and experimental studies of ribavirin therapy concluded that, although most reports claimed a therapeutic benefit, the quality of the evidence was low (Soares-Weiser et al, 2010). The authors concluded that ''a randomized controlled trial in the context of good quality supportive care is justified.''…”
Section: Ribavirinmentioning
confidence: 99%
“…The use of ribavirin for the treatment of CCHF has been reviewed in detail in two recent articles (Soares-Weiser et al, 2010;Keshtkar-Jahromi et al, 2011). The drug was first employed in 1985, when it was given as postexposure prophylaxis in a nosocomial outbreak in South Africa (van de Wal et al, 1985).…”
Section: Ribavirinmentioning
confidence: 99%
“…However, ribavirin (Virazole) is the only antiviral drug used against CCHFV, which is only effective in certain cases (61). Despite the verified insufficient efficacy of ribavirin for CCHF patients by two systematic reviews and meta-analyses, the World Health Organization has approved antiviral ribavirin for treatment of CCHFV infection based on in vitro data (7,60,62,63). Ribavirin can be taken orally and intravenously.…”
Section: Treatmentmentioning
confidence: 99%